The Efficacy of Biofeedback Treatment in Patients with Fecal Incontinence - Ömer Öztürk; Yasemin Özin; Ferhat Bacaksız; İlyas Tenlik and Derya Arı and Volkan Gökbulut and Özlem Akdoğan and Mahmut Yüksel and Bayram Yeşil and Zeki Mesut Yalınkılıç (Turkish Journal of Gastroenterology, 2021)
Background: The initial treatment for fecal incontinence (FI) includes supportive treatment and medical treatment. If the initial treatment fails, biofeedback therapy (BFT) is recommended. However, there are limited and conflicting results in the literature supporting the beneficial effect of BFT for FI. The aim of the study is to analyze the efficacy of BFT in 126 patients who have FI due to several causes. Methods: The data of 126 patients (88 females (69.8%) and 38 males (30.2%)) were collected retrospectively. Colonoscopy, anorectal manometry (ARM), and 3D-Endoanal ultrasonography (EAUS) were performed for all patients before applying BFT. In addition, all patients received toilet training instruction and training in Kegel and other pelvic floor strengthening exercises from an experienced nurse, before BFT. Results: The median age of participants was 54 years (range 18-75 years). While 80 patients (63.5%) had clinical and manometric benefit from BFT, 46 patients (36.5%) did not respond to BFT. According to the EAUS and ARM findings, BFT was beneficial in patients who had partial external sphincter failure, and was unsuccessful in patients who had both internal and external sphincter failure, both internal and external sphincter tears, and external sphincter tear rates of more than 25%. After BFT, significant increases in squeeze pressures were observed, with this increase being higher in the positive-response group. Conclusion: The results suggest that BFT is effective in the treatment of FI for specific patient populations. Cite this article as: Öztürk Ö, Özin Y, Bacaksız F, et al. The efficacy of biofeedback treatment in patients with fecal incontinence. Turk J Gastroenterol. 2021; 32(7): 567-574.